Rapid tempering of sucrose-free milk chocolates by βV seeding: textural, rheological and melting properties - Konar, Nevzat; Oba, Sirin; Toker, Omer Said; Palabiyik, Ibrahim; Goktas, Hamza; Artik, Nevzat; Sagdic, Osman (SPRINGER, 2017)
In the present study, it was aimed to produce sucrose-free milk chocolate including isomalt or maltitol by beta(V) seeding technique as an alternative to conventional tempering process which was performed by using temper machine (47-27-32 degrees C). For this aim, conched milk chocolates were melted and crystallized with beta(V) seeds added at different concentrations (0.5, 0.6, 0.7, 0.8, 0.9 and 1.0 g/100 g chocolate). The influence of beta(V) seed concentrations on the textural, rheological and melting properties of the end products was investigated, and the results were compared with those of conventional sucrose-free milk chocolates. Hardness value of isomalt including samples decreased at beta(V) seeds concentrations of 0.7, 0.8, 0.9 g/100 g chocolate. For the maltitol containing samples it increased significantly at 0.9 g/100 g chocolate compared to traditional chocolate. However, generally, hardness value of the samples varies in a narrow range by seeding technique. Milk chocolate samples containing maltitol were found to have higher hardness values than isomalt containing chocolate samples (p < 0.05). Melting characteristics of the samples were not affected by beta(V) seed concentrations. According to casson model, seeding at 1 g/100 g chocolate for maltitol samples and 0.9 g/100 g chocolate for isomalt samples significantly increased yield stress compared to control samples. However, by seeding technique yield stress only varied between 2.48 and 5.91 Pa. Therefore, the findings of this study showed that it is possible to produce sucrose-free chocolates by tempering with beta(V) seeds with desired quality similar to sucrose-free milk chocolate produced by using conventional tempering.
Keywords: Chocolate; Isomalt; Maltitol; Seeding; Tempering; DARK CHOCOLATE; COCOA BUTTER; PRECRYSTALLIZATION PROCESS; CRYSTALLIZATION; SUGAR; SWEETENERS; IMPACT; Food Science & Technology